Review of Camprubí, Lino, Engineers and the Making of the Francoist Regime, Cambridge, MA: The MIT Press, 2014, 320 pp., 40 monochrome illustrations and photographs - Ongay de Felipe, Íñigo (2018)
Fil: Ongay de Felipe, Íñigo. Fundación Gustavo Bueno; España.